The Ants of the Genus Lasius (Hymenoptera, Formicidae) from Late Eocene European Ambers - Dlussky, G.M. (Вестник зоологии, 2011)
Finds of the genus Lasius Fabricius in the Baltic, Bitterfeldian, Rovno, and Scandinavian Ambers (Late Eocene) are revised. Neotypes of L. pumilus Mayr, 1868 and L. punctulatus Mayr, 1868 are designated. A key to workers and gynes of Lasius species from the Late Eocene European ambers is compiled. All Lasius species from these ambers belong to the subgenus Lasius s. str. L. schiefferdeckeri Mayr, 1868 is one of most abundant ant species in the Late Eocene European ambers: it consists 15.2—19.5% of all ant specimens in Baltic Amber, 24.5% in Bitterfeldian Amber, 23.8% in Rovno Amber, and 23.6% in Scandinavian Amber of the examined collections. Based on the features of fossilization of this species, it is possible to assume that at least in part it constructed arboreal nests and made roads to aphids’ colonies. The list of nine ant species found in syninclusions with L. schiefferdeckeri is provided.